The Impact of the Interventions for 4+ Antenatal Care Service Utilization in the Democratic Republic of Congo: A Decision Tree Analysis - Hocheol Lee; Sung Jong Park; Grace O. Ndombi; Eun Woo Nam (Ubiquity Press, 2019)
Background: In 2015, the United Nations set the sustainable development goals (SDGs) with a focus on the maternal mortality ratio (MMR), to decrease the mortality rate of newborns to 70 per 100,000 by 2030. Despite efforts to achieve the SDGs, the MMR in the Democratic Republic of Congo (DRC) was 693 per 100,000 in 2015-the sixth highest in the world and higher than the average (547 per 100,000) of sub-Saharan Africa. Objectives: The primary aim was to identify effect factors of 4+ antenatal care (ANC) of the maternal and child health care (MCH) project focused on reproductive women in the DRC. Methods: This study used a before and after study design and focused on ANC utilization of reproductive age women in Kenge, DRC. This study provided the MCH intervention based on three phases of the Three Delays Model from 2014 to 2017. We interviewed 2,663 participants from 2014 to 2017. This study used the decision tree node for prediction of 4+ ANC utilization. Findings: The decision tree showed that hand-washing (1.000) was the most important factor for receiving 4+ ANC services in the midline I survey, followed by writing skills (0.891), satisfaction with health facilities (0.869), age (0.782), and awareness of interventions (0.621). The results of the midline II decision tree demonstrated that MCH promotion by signboard (1.000) was the most important factor for 4+ ANC services, followed by income (0.970), and abortion (0.894). In the third year, distance (1.000) was the most important factor, followed by abortion (0.940) and knowledge of exclusive breastfeeding (0.806). Conclusions: The most important factors were related to awareness. We recommend conducting interventions focused on improving awareness increase 4+ ANC utilization. Sustainability intervention for improving the 4+ ANC utilization requires that focus on the infrastructure, such as accessibility and knowledge, of reproductive women.